ESTRESSE CRÔNICO OCUPACIONAL EM MULHERES POLICIAIS PENAIS - NAYLA CRISTINA SANTIAGO DA SILVA (2024)
Chronic occupational stress is associated with several adverse health effects, which are partially mediated by cortisol, which is the end hormone of the HPA axis and it is involved in the regulation of several bodily processes. From this perspective, the general objective of this work was to evaluate the expression of chronic occupational stress in female criminal police officers in the cities of Rio Brilhante and Dourados. An exploratory research was carried out, with a cross-sectional design and quantitative approach, by measuring hair cortisol levels and applying instruments. Regarding the expression of measured hair cortisol, 88% of the participants had levels below normal. There was no association between the level of hair cortisol and the presence of BS, nor with the BS subscales. The data demonstrated the presence of BS in 14.7% (95% CI: 7.6% to 24.7%) of the participants, especially in younger women, those without children and those who work in the care sector. There was an association between a high level of emotional exhaustion and working in the care area, drinking alcohol, and not practicing physical activity; between the low level of professional achievement and the age group and number of children; between the high level of depersonalization and working in the assistance area and the consumption of alcoholic drinks. Around 70% of the servers presented levels of vulnerability to stress, higher, and upper medium in Factor 1 (Climate and organizational functioning). There was a higher mean pain intensity score in criminal police officers with a higher to upper medium level of vulnerability to stress compared to the medium to lower level, however, there was no difference regarding hair cortisol values. The relationship between postural discomfort and occupational stress has not yet been conclusively established in the literature, however, it is plausible to propose its contribution to postural discomfort and musculoskeletal symptoms. The results highlighted the need for attention to the mental health of these professionals and the development of strategies that minimize the harmful effects of prison work. Decs: burnout psychological; hydrocortisone; occupational stress